The Effect of Work-Family Conflict Mediation on the General Quality of Life and the Quality of Working Life in Employed Women - Mohtaram Zabihi; Ghahraman Mahmoudi; Ghassem Abedi (Shahid Sadoughi University of Medical Sciences, 2018)
Background: General life quality and its impact on the quality of working life are among the most important and critical issues in today's organizations. Work-family conflict is an important phenomenon that affects both employees and employers. This study aims to determine the relationship between general life quality and the quality of working life in working women with the role of work-family conflict mediation. Methods: This descriptive-analytical study was conducted in 2017. The study population was 4266 women working in the health department of Mazandaran University of Medical Sciences. In this study, 351 samples were selected by stratified sampling method in 11 cities of 19 provinces of Mazandaran province. Data were collected using the World Health Organization Quality of Life Questionnaire (WHOQOL-BREF) with 26 questions, Casio quality of work life questionnaire with 29 questions, and Carlson work-family conflict with18 questions. The results were analyzed using SPSS 24 and AMOS 22 softwares. Furthermore, Kolmogorov-Smirnov tests, structural equation model, path analysis and standard coefficients, Chi-square, fit index, Bootstrap, and Sobel tests were utilized. Results: Demographic data included age, education, marital status, professional background, employment status, household size, job title, and income. The relationship between general quality of life and quality of working life in employed women was significant (P-value = 0.009). There was a significant and negative relationship between life quality and work-family conflict (P-value = 0.009). The effect of mediating variable of work conflict, between general quality of life and specific quality of working life was not statistically significant (P-value = 0.009). Conclusion: Since general quality of life has a direct effect on the quality of working life in employed women, proper planning and training courses on time management, life and problem solving skills for employees, especially women working in the health sector can improve general  life quality as well as  quality of working life and reduce their work conflicts.